Impact Of Nursing Interventions On Prevention Of Ventilator-Associated Pneumonia In Intensive Care Units: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Ventilator-associated pneumonia (VAP) remains a serious healthcare-associated infection in intensive care units (ICUs), contributing to increased morbidity, mortality, prolonged hospital stays, and elevated healthcare costs. Nurses play a central role in VAP prevention through continuous bedside care and implementation of evidence-based preventive interventions. This systematic review aimed to synthesize evidence on the impact of nursing interventions on VAP prevention among mechanically ventilated adult patients in ICUs.Methods: A systematic review was conducted following PRISMA guidelines. Electronic searches of PubMed, CINAHL, Scopus, ScienceDirect, and Google Scholar were performed to identify studies published within the last two decades. Studies evaluating nursing-led interventions including oral care protocols, patient positioning, ventilator care bundles, and nurse education programs were included. Two reviewers independently screened articles, extracted data, and assessed methodological quality using appropriate critical appraisal tools. Due to heterogeneity across studies, a narrative synthesis was conducted.Results: Eight studies met the inclusion criteria, comprising randomized controlled trials, quasi-experimental studies, observational studies, and systematic reviews. Structured oral hygiene interventions consistently reduced VAP incidence, with one study reporting a decrease from 44.6% to 34.3% (OR=0.65) and another demonstrating significant reduction (P=0.015). A meta-analysis reported an odds ratio of 0.61 for antiseptic oral care. Ventilator care bundles reduced VAP rates by over 36% when fully implemented. Nurse compliance with prevention guidelines ranged from 84.6% to 85.9%, with improved adherence following educational interventions. Head-of-bed elevation (≥30°) significantly reduced aspiration risk.Conclusion: Nursing interventions, including structured oral hygiene protocols, ventilator care bundles, proper patient positioning, and nurse education programs, significantly reduce VAP incidence in ICU settings. Consistent implementation of these evidence-based strategies, supported by ongoing training and compliance monitoring, is essential for improving patient outcomes, reducing healthcare costs, and enhancing quality of care in mechanically ventilated patients.